Privatization and gender discrimination: the chilean pension system study case - Chamorro, Sabina (Papeles de Europa, 2019)
The privatization of the public pension system by the authoritarian regime of Pinochet in Chile in 1981 increase the poverty among its pensioner population, affecting women in particular. Through an empirical analysis grounded in feminist theory, the present research confirms that the Chilean pension system generates discrimination against women directly and indirectly, and intensifies gender duality regarding integration into the system.